Synthesis, Characterization, and Electrochemical Study of Novel Porphyrin Derivatives as Corrosion Inhibitors for Carbon Steel in HCl Solutions - Mohammed Thamer Jaafar; Luma Majeed Ahmed; Rahman Tama Haiwal (Indonesian Journal of Chemistry, 2024)
This study involves the synthesis of some porphyrins derivatives, these are termed as 4,4',4'',4'''-(porphyrin-5,10,15,20-tetrayl)tetrakis(N-(6-aminoacridin-3-yl)benzamide) (3a), 4,4',4'',4'''-(porphyrin-5,10,15,20-tetrayl)tetrakis(N-(5-methoxybenzo[d]thiazol-2-yl)benzamide) (3b), 4,4'-(10,20-bis(3-hydroxyphenyl)porphyrin-5,15-diyl)bis(N-(6-aminoacridin-3yl)benzamide) (5a), and 4,4'-(10,20-bis(3-hydroxyphenyl)porphyrin-5,15-diyl)bis(N-(benzo[d]thiazol-2-yl)benzamide) (5b). These derivatives were synthesized using open circuit potential (OCP) and potentiodynamic polarization (PDP) in 0.1 M HCl solution methods. These derivatives were characterized using nuclear magnetic resonance (1H- and 13C-NMR) spectroscopy, mass spectra (ESI), and micro elemental analysis (CHN). The activity of these synthesized materials was investigated as a corrosion inhibitor using carbon steel (CS) as a model for corroded materials. The obtained results showed that the synthesized porphyrins derivatives were effective corrosion inhibitors to 0.1 M HCl solution for CS. In the case of the derivative 3a, a maximum inhibition efficiency (IE%) was recorded and it was around 74%. The derivative 3b showed an IE% of around 68.11%, while the %IE of 5a and 5b were around 18.98% and 45.16%, respectively. The best IE% value that was recorded for the derivative 3a has the potential to be effective anticorrosive coatings for industrial applications and act as mixture inhibitor because their ΔEcorr values are less than 85 mV. On the CS surface following treatment with compound 3a, the inhibitor mechanism for acidic medium (HCl) was investigated.